University of Salento’s transactional relations: assessing the knowledge transfer of a public university in Italy - Calignano, Giuseppe; Quarta, Cosimo Alessandro (ERDKUNDE, 2014)
Salento is an interprovincial area in Apulia (South Italy) formed by the three provinces of Lecce, Brindisi and Taranto. Salento is an economically heterogeneous area that is characterised by large businesses and hi-tech companies as well as a myriad of medium, small and very small traditional manufacturing firms. In this socio-economic framework, the role of the only public university in the area is critical to local development: in the post-industrial era, knowledge transfer is crucial for the diffusion of innovation and competitiveness of regional systems. This work uses a new empirical approach to track the relations between the University and the marketplace to precisely describe the extent to which research performed at the university meets the needs of near and far commissioners. Our analysis demonstrates that the majority of the knowledge produced by a public University remains within the region/local area and that the distribution of clients follows different patterns depending on whether they are public or private entities. Furthermore, through our analysis it has been possible to assess both the intensity (quantity of research) and frequency (number of relations) of transferred knowledge.